The Effectiveness between Emoticons and Traditional Figures on Presenting Accounting Information - Kusumasari, Lita; Wahyu Anggoro, Kusumasari; ., Miswanto (International Journal of Engineering and Technology, 2018)
Accounting is business language. A language has two components that are symbol and grammatical rule. Accounting information usually presented as the set of procedures for creating financial reports. Based on framework for the preparation and presentation of financial statements, information provided in financial statements are useful to users if it has qualitative characteristics. One of the characteristics is understandability. For this purpose, users are assumed to have a reasonable knowledge of business and economic activities and accounting and a willingness to study the information with reasonable diligence. Accounting information usually presents as numbers and conventional graph. Previous studies suggest that schematic faces is used as alternative communication for accounting information. Existing application of schematic faces is found by Chernoff. In the modern age, people is get used to know emoticon as symbol for communicate easily, so this paper employs emoticon not the Chernoff faces. This research is aimed to know the impacts on the effectiveness between emoticon and traditional figure on presenting accounting information.  The analysis of company net income, current ratio, liquidity ratio, return on asset and earning per share are presented in traditional figures and emoticons. Respondent has to find out which company is better performance compare to the other. Method of analysis are descriptive statistic and differential t-test. Respondents are accounting and management students which are taken by purposive random sampling. The result show that respondents have better average score on choosing the better company using emoticon (88.18) compares to traditional figure (82.72). The effectiveness of financial information is also significantly evidenced in emoticons compare to traditional figure.